Exploring New Inflammatory Biomarkers and Pathways during LPS-Induced M1 Polarization. (21st December 2016) - Cunha, Carolina; Gomes, Cátia; Vaz, Ana Rita; Brites, Dora
Abstract : Identification of mediators triggering microglia activation and transference of noncoding microRNA (miRNA) into exosomes are critical to dissect the mechanisms underlying neurodegeneration. We used lipopolysaccharide- (LPS-) induced N9 microglia activation to explore new biomarkers/signaling pathways and to identify inflammatory miRNA (inflamma-miR) in cells and their derived exosomes. Upregulation of iNOS and MHC-II (M1-markers) and downregulation of arginase 1, FIZZ1 (M2-markers), and CX3CR1 (M0/M2 polarization) confirmed the switch of N9 LPS-treated cells into the M1 phenotype, as described for macrophages/microglia. Cells showed increased proliferation, activated TLR4/TLR2/NF- κ B pathway, and enhanced phagocytosis, further corroborated by upregulated MFG-E8. We found NLRP3-inflammasome activation in these cells, probably accounting for the increased extracellular content of the cytokine HMGB1 and of the MMP-9 we have observed. We demonstrate for the first time that the inflamma-miR profiling (upregulated miR-155 and miR-146a plus downregulated miR-124) in M1 polarized N9 cells, noticed by others in activated macrophages/microglia, was replicated in their derived exosomes, likely regulating the inflammatory response of recipient cells and dissemination processes. Data show that LPS-treated N9 cells behave like M1 polarized microglia/macrophages, while providing new targets for drug discovery. In particular, the study yields novel insights into the exosomal circulating miRNA during neuroinflammation important for emerging therapeutic approaches targeting microglia activation.